Effect in vitro of metabolized praziquantel on Schistosoma japonicum - Shen Pei-lin; Qian Xie-ming; Zhang Yan-ping; Xu Jian-man; Ye Jia-fu (Acta Pharmacologica Sinica, 2016)
After incubating praziquantel with mouse liver homogenates at 37℃ for 2 h, the antischistosomal activity decreased significantly. When praziquantel was incubated with mouse liver homogenates which were previously induced with phenobarbital, the antischistosomal activity disappeared. After incubation, praizquantel was determined spectrophotometrically at 264.5 nm. Normal liver contained 32% of original praziquantel, while induced liver contained none. It was suggested that the active form was the unchanged praziquantel.